Implementasi Transnational Advocacy Networks Gerakan Earth Hour dalam Merespon Isu Perubahan Iklim di Indonesia - Resti, Beatris; Wicaksono, Arief (Journal of International and Local Studies, 2024)
Today the issue of climate change is a problem that needs to be responded collectively. Various movements emerged to respond this problem, among the most known movements is Earth Hour which influence is now became more relevant in Indonesia. This research aims to analyze and find out how Earth Hour has been implemented in Indonesia since 2009 in overcoming climate change using the Transnational Advocacy Networks (TAN) concept. Using qualitative method, researchers will describe the correlation between the data obtained and the TAN concept to explain Earth Hour in its efforts to overcome climate change in Indonesia. In using the TAN concept, researchers found that Earth Hour together with WWF Indonesia carries out all four TAN advocacy network strategies, namely, information politics, symbolic politics, leverage politics and accountability politics.